Analisis Manajemen Promosi sebagai Strategi Pengembangan UMKM Toko Sembako Te Kokom - Ramadhan Wijaya; M Rifaldi ilham Firmansyah; Nuris Sanida (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze marketing strategies that can be applied by UMKM Te Kokom in facing business competition in the digital era and in enhancing business competitiveness and sustainability. The rapid development of information technology and changes in consumer behavior require micro, small, and medium enterprises (MSMEs) to adapt through the implementation of effective and innovative marketing strategies. This research employs a descriptive qualitative approach, with data collected through direct observation of business activities and a literature review of relevant scientific sources. The findings indicate that appropriate marketing strategies for UMKM Te Kokom include the utilization of digital media as a promotional and communication tool, strengthening product quality and differentiation, implementing competitive pricing strategies, expanding distribution channels, and applying promotion strategies focused on customer loyalty. The use of social media is proven to increase market reach and foster more interactive communication with consumers, while product innovation and high-quality service enhance customer satisfaction and trust. The study concludes that the implementation of integrated and sustainable marketing strategies plays a crucial role in increasing sales volume, expanding market share, and maintaining the business existence of UMKM Te Kokom amid increasingly dynamic competition. This research is expected to serve as a reference for MSME practitioners in formulating adaptive, market-oriented marketing strategies.